Gender, the Demotic and the Cinema in the Early Adelphi (1923-1924): The Iris Barry Moment - Noëlle Cuny (Études Britanniques Contemporaines, 2016)
The Adelphi (1923-27 then 1927-55), John Middleton Murry’s London magazine, was culturally conservative in its initial conception, whether in its contributor line-up or in its representations. The marginal space women’s writing originally received in its pages, aside from the posthumous pieces by Katherine Mansfield, belied the professed inclusiveness of the project; it was also riddled with allusions to the ‘eternal feminine’ or to the devouring mother figure. The rampant undervaluation of all things feminine reflected a similar hierarchy in the arts, with cinema—a ‘monstrous weed’ (Lawrence)—at the very bottom of the scale. It took an energetic, fearlessly committed journalist such as Iris Barry, in the spring of 1924, to impose serious discussion of the cinema in the magazine, a discussion which, though intimate and conversational in tone, was eminently moral and political. One of the earliest professional critics to write on Karl Grune’s The Street or on Chaplin’s The Woman of Paris, Iris Barry posits the possibility of edification through pleasurable sensation and announces the advent of the viewer (as opposed to the voyeur). Her views anticipate Siegfried Kracauer’s 1927 essay on the cinema as distraction, that is, as a mode of non-bourgeois self-discovery. In the Adelphi, the figure of the woman cinema critic and serious cinema itself co-emerged symbiotically, thus ushering this middlebrow magazine into a modernity it hitherto resisted.